Efecto del método de cocción sobre la concentración de metales pesados en Hoplias malabaricus (Erythrinidae): Effect of cooking method on heavy metal concentrations in Hoplias malabaricus (Erythrinidae) (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
Impacts of mining and agriculture have turned mercury (Hg), methylmercury (MeHg), zinc (Zn), cadmium (Cd), lead (Pb) and copper (Cu) into common pollutants in the fish and ecosystem compartments of Colombian wetlands. For this reason, in this study we evaluated concentrations of these metals in Hoplias malabaricus muscle, and determining their variations according 5 cooking methods (Smoked, Fried, Stew, Viuda and Salpicón). The concentrations were determined by thermal decomposition, amalgamation and atomic absorption spectroscopy (EPA-7473) (Hg-MeHg), atomic absorption spectroscopy with flame (FLAAS) (EPA-7000B) (Zn-Cu) and atomic absorption spectroscopy in graphite furnace (GFAAS) (EPA-7010) (Pb-Cd).We found Zn was the metal most accumulated in this tissue, likewise Cd (Fried, Viuda, Smoked and Salpicón) and Pb (Salpicón) exceeded maximum permissible limits (EU, 2018) and FAO (1992) for mean concentrations in fish muscle for human consumption. Similarly significant differences (p